Radio Liberty in the Context of EU-Russio-US Relations - Loeser, Henry G. (2008)
The evolution of democracy in the EU’s eastern neighbor Russia is retarded and still struggling to gain traction in the face of stubborn resistance. The lack of a functioning civil society, rule of law, true market economy, pluralism, respect for human rights, and media freedom are in direct contrast to European Union policies. Questions of EU-Russia-US relations in areas of energy security, immigration, criminal enterprise, terrorism, and weapons of mass destruction all pose serious threats to regional stability and subsequent European security. United States foreign policy is an important actor in this sphere, using instruments such as the venerable Cold War-era Radio Liberty to project its values and interests. But therein lies the question: What is the role of Radio Liberty in the changing Russian media landscape and what impact does it impart to EU-Russia-US Relations?.